Urena lobata (PEMANFAATAN SEBAGAI OBAT TRADISIONAL DAN BIOAKTIVITASNYA) - Marina Silalahi (J-KESMAS: Jurnal Kesehatan Masyarakat, 2020)
Urena lobata  is one of the Malvaceae family that has long been used as medicine. This plant is easy to find on the roadside or empty land because it is one of the pioneering vegetation plants, therefore it is very potential to be developed as traditional medicine. The purpose of writing this article is to explain the relationship between the utilization and bioactivity of U. lobata. The method used in writing this article is a review and review of the literature published online. In ethnobotany, U. Lobata is used for fever, rheumatism, wounds, and as an antiseptic. Urena lobata but prominent bioactivity is antimicrobial, antifertility, anti-diabetes Mellitus, and hepatoprotective. The potential and bioactivity of U. lobata as an antifertility for further investigation so that it can be developed to regulate the number of births and is reversible.